Mediterranean diet – promotion and dissemination of healthy eating: proceedings of an exploratory seminar at the Radcliffe institute for advanced study. (17th February 2022) - Sotos-Prieto, Mercedes; Del Rio, Daniele; Drescher, Greg; Estruch, Ramon; Hanson, Chavanne; Harlan, Timothy; Hu, Frank B.; Loi, Maria; McClung, James P.; Mojica, Angelo; Puglielli, Daniela; Toong, Ken; et al.
Abstract: The traditional Mediterranean diet is considered the world's most evidence-based eating pattern for promoting health and longevity. However, institutional food environments and their busy consumers often sacrifice health benefits for the convenience of faster and cheaper foods that generally are of lower quality and are more processed, and thus, contribute to the current epidemics of obesity and diabetes. Expert consensus has even identified the Mediterranean diet as the easiest to follow among healthy eating patterns. Nonetheless, fewer American families cook at home and many food services have been slow to implement healthier food options compatible with the Mediterranean diet. In September 2019, we convened a group of thought leaders at an exploratory seminar entitled: "Mediterranean Diet: Promotion and Dissemination of Healthy Eating", hosted by the Radcliffe Institute for Advanced Studies at Harvard University. The multidisciplinary faculty discussed best practices for translating traditional Mediterranean lifestyle principles to modern society.